EFEKTIVITAS METODE PEMBELAJARAN AKTIF TIPE GROUP TO GROUP EXCHANGE DALAM MENINGKATKAN HASIL BELAJARA SISWA PADA MATA PELAJARAN PEMUPUKAN DI SMKN 4 JENEPONTO - Mubarak, Ahmad Zaky; Rais, Muhammad; Nurmila, Nurmila (Jurnal Pendidikan Teknologi Pertanian, 2018)
This study aims to determine the effectiveness Level of active learning method (Active Learning) on the fertilization subjects at students class XI Agribusiness Nursery and Culture Network SMKN 4 Jeneponto. This research is a quasi experimental in the form of one group pre-test post-test design with 24 people Population and the whole population used as sample. Data obtained by documentation, test, and observation techniques. The research procedure includes the stages: pre-test, treatment, post-test. From the results of research shows that the application of active learning method (Active Learning) effectively used in improving student achievement in the fertilization subjects class XI APKJ 2 SMKN 4 Jeneponto, Jeneponto district. Based on statistical analysis, this study shows the classical learning completeness in the pre-test is 20.83%, the post-test has increased to 87.50% with the level of effectiveness learning demonstration Method is 78.13 scale 100